Spinal cord stimulation prevents paclitaxel-induced mechanical and cold hypersensitivity and modulates spinal gene expression in rats. (September 2019) - Sivanesan, Eellan; Stephens, Kimberly E.; Huang, Qian; Chen, Zhiyong; Ford, Neil C.; Duan, Wanru; He, Shao-Qui; Gao, Xinyan; Linderoth, Bengt; Raja, Srinivasa N.; Guan, Yun
Abstract: Introduction: Paclitaxel-induced peripheral neuropathy (PIPN) is a common dose-limiting side effect of this cancer treatment drug. Spinal cord stimulation (SCS) has demonstrated efficacy for attenuating some neuropathic pain conditions. Objective: We aim to examine the inhibitory effect of SCS on the development of PIPN pain and changes of gene expression in the spinal cord in male rats after SCS. Methods: We examined whether traditional SCS (50 Hz, 6–8 h/session daily for 14 consecutive days) administered during paclitaxel treatment (1.5 mg/kg, i.p.) attenuates PIPN-related pain behavior. After SCS treatment, we performed RNA-seq of the lumbar spinal cord to examine which genes are differentially expressed after PIPN with and without SCS. Results: Compared to rats treated with paclitaxel alone (n = 7) or sham SCS (n = 6), SCS treatment (n = 11) significantly inhibited the development of paclitaxel-induced mechanical and cold hypersensitivity, without altering open-field exploratory behavior. RNA-seq showed that SCS induced upregulation of 836 genes and downregulation of 230 genes in the spinal cord of paclitaxel-treated rats (n = 3) as compared to sham SCS (n = 5). Spinal cord stimulation upregulated immune responses in paclitaxel-treated rats, including transcription of astrocyte- and microglial-related genes, but repressed transcription of multiple gene networks associated with synapse transmission, neuron projection development, γ-aminobutyric acid reuptake, and neuronal plasticity. Conclusion: Our findings suggest that traditional SCS may attenuate the development of pain-related behaviors in PIPN rats, possibly by causing aggregate inhibition of synaptic plasticity through upregulation and downregulation of gene networks in the spinal cord. Abstract : Supplemental Digital Content is Available in the Text.